Nonadrenal epinephrine-forming enzymes in humans. Characteristics, distribution, regulation, and relationship to epinephrine levels. - Kennedy, B (1995)
Animal studies indicate that nonadrenal tissues may synthesize epinephrine (E). Here we demonstrate phenylethanolamine N-methyltransferase (PNMT) and/or nonspecific N-methyltransferase (NMT) enzymatic activity in human lung, kidney, heart, liver, spleen, and pancreas. There was a significant overall correlation (r = 0.34) between tissue PNMT and E. PNMT and NMT in human tissues differed in substrate and inhibitor specificity, thermal stability, and antigenicity. By these criteria, PNMT in human lung and in human bronchial epithelial cells were indistinguishable from adrenal PNMT. PNMT and/or NMT activity were present in red blood cells (RBCs), and cancer cell lines. Human kidney, lung, and pancreas showed immunohistochemical staining with an antibody to adrenal PNMT. RBC PNMT activity was lower in males than females and was increased in hyperthyroidism and decreased in hypothyroidism. PNMT activity in a human bronchial epithelial cell line was dramatically increased by incubation with dexamethasone. E and 3H-E levels in plasma and urine during an intravenous infusion of 3H-E into humans indicated that kidney may synthesize half of urinary E. We conclude that PNMT and NMT are widely distributed in human tissues, that they may synthesize E in vivo and are influenced by glucocorticoid and thyroid hormones.